The Implementation of Talking Stick Learning Model to Improve Learning Outcomes of Islamic Religious Education Subjects for Students at SDN 40 Bengkulu Selatan - Mike Adi Putra; Aam Amaliyah (Jurnal Indonesia Pendidikan Profesi Guru, 2024)
Objective: The purpose of this study was to determine the influence of the Talking Stick learning model in improving student learning outcomes in Islamic Religious Education (PAI) at SDN 40 Bengkulu Selatan. Method: This research employed a Classroom Action Research (CAR) approach conducted in 2023 at SDN 40 Bengkulu Selatan. The study involved 12 fourth-grade students. Data collection techniques included observation, questionnaires, tests, and non-test instruments such as observation sheets. The data were analyzed using a non-statistical or qualitative analysis method. Result: The findings revealed that the application of the Talking Stick learning model effectively improved student learning outcomes in PAI subjects. Students showed increased participation, engagement, and understanding of the material. The model fostered an interactive and dynamic learning environment that supported better academic performance. Conclusion: The Talking Stick learning model is a beneficial strategy in Islamic Religious Education, as it not only enhances student learning outcomes but also promotes active participation and collaboration among students. Contribution: This study contributes to the development of innovative teaching strategies in Islamic Religious Education. It highlights the potential of active learning models like Talking Stick to make PAI learning more engaging and effective, beyond its traditional focus on Islamic law and moral values.